2009
DOI: 10.1007/s00442-009-1416-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simulated herbivory on water relations of aspen (Populus tremuloides) seedlings: the role of new tissue in the hydraulic conductivity recovery cycle

Abstract: Physiological mechanisms behind plant-herbivore interactions are commonly approached as input-output systems where the role of plant physiology is viewed as a black box. Studies evaluating impacts of defoliation on plant physiology have mostly focused on changes in photosynthesis while the overall impact on plant water relations is largely unknown. Stem hydraulic conductivity (k(h)), stem specific conductivity (k(s)), percent loss of hydraulic conductivity (PLC), CO(2) assimilation (A) and stomatal conductance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…A quadrupling or doubling in G Cref after defoliation as was shown here for Q. prinus and Q. velutina , was also observed for g S in Populus tremuloides in a simulated defoliation experiment (Gálvez and Tyree, 2009). Thus, trees compensate for leaf area losses and reduced CO 2 uptake by capitalizing on higher water availability for the remaining leaves.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A quadrupling or doubling in G Cref after defoliation as was shown here for Q. prinus and Q. velutina , was also observed for g S in Populus tremuloides in a simulated defoliation experiment (Gálvez and Tyree, 2009). Thus, trees compensate for leaf area losses and reduced CO 2 uptake by capitalizing on higher water availability for the remaining leaves.…”
Section: Discussionsupporting
confidence: 81%
“…It is well known that stomata close under drought conditions to prevent further water loss (Alder et al, 1996; Cochard et al, 1996; Sperry et al, 1998), but less is known about how stomata respond to disturbance. Some leaf-level investigations suggest an increase in photosynthesis after defoliation as a means to compensate for lost leaf area (VanderKlein and Reich, 1999; Wallin et al, 2003; Turnbull et al, 2007; Delaney, 2008; Gálvez and Tyree, 2009). However, the scaling of individual leaf responses to the entire canopy is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distal plant parts are arguably expendable; their sacrifice can help to maintain favourable plant water balance by reducing the total transpiring surface (Rood et al ., 2000). This strategy might be particularly vital in poplar which is well known for its ability to regenerate by root suckering and re-sprouting from auxiliary buds (Galvez and Tyree, 2009; Lu et al ., 2010). Nevertheless, it is questionable whether such reasoning is relevant to the relatively young saplings measured in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…cavitation), as many other studies have shown (e.g. Spooner et al, 2002;Smale et al, 2005;Gálvez and Tyree, 2009;Morales et al, 2015).…”
Section: Effect Of Fragmentation On Survivorship and Growth Of B Tawmentioning
confidence: 83%